Contract of payment protection insurance - Petrović-Tomić Nataša (Anali Pravnog Fakulteta u Beogradu)
Although fairly widespread in the practice of domestic banks, payment protection insurance represents something very unknown to the average consumer of financial services. Author intends to explain mechanism of mentioned product of insurance with emphasis on potential negative effects notices in the practice of insurance. Since the author gives enough arguments in favour of the statement that credit consumer is vulnerable consumer she proposes the introduction of saving component in payment protection insurance which covers death of the insured person. The point is to harmonize our law with comparative law. In order to secure better protection of insured it is recommended to expand insurance coverage. Author concludes that payment protection insurance currently represents highly risky transaction in Serbian practice of insurance, concluded contrary to the interests of insured. It is necessary to revise the general conditions of insurance of domestic insurers as well as oblige banks to meet legal obligations, especially the duty to inform insured.